12/#404 The impact of 2020 COVID-19 outbreak on the treatment patterns of cervical cancer in Brazilian public health system. (4th December 2022) - Borba, Maria Amelia; Rego, Maria Aparecida; Almeida, Milena Falcão; Zuppo, Isabella; Gomes, Mariana; Batista, Paula; Nadalin, Michelle; Rodrigues, Angelica
Abstract : Objectives: To evaluate Covid-19 pandemic impact on treatment patterns of cervical cancer (CC) in Brazilian public health system. Methods: This real-world retrospective study used DATASUS datasets. Female aged ≥18 years with claims of CC (ICD-10-C53.*) were identified from January/2014-December/2020. Non-advanced (naCC – stage 1 and 2) and advanced (aCC – stage 3 and 4) were evaluated and compared treatment patterns in 2014–2019 vs 2020. Results: A total of 206, 861 women were included, being 26, 815 in 2020 (49% newly diagnosed). 25.8% of the patients in 2020 had only surgery, compared to 39.2% in the period 2014–2019. The treatment patterns were evaluated only in the staged patients that corresponded to 44% (90, 073) in the full cohort, and 75.8% in 2020's cohort. The overall proportion of 40% naCC and 60% aCC didn't change much in 2020, but key differences were observed in treatment patterns. The use of radiation (with/without surgery or chemo) was reduced in about 25%, notably from 87% to 62% and 61% in stages 1 and 2, respectively. Similarly, surgery (with/without radiation or chemo) reduced in all stages, 18% in stage 1. Isolated chemo adoption, in the other hand, increased in 2020 for all stages by an average of 22.6%, including in naCC, where for stage 1 patients increased from 7.7% to 30.2%. Conclusions: This study undercovers the CC treatment gaps caused by Covid-19, from which the long-term impact still to be determined. The curative approaches were reduced due to hospitals collapse and may impact patient's outcomes.